PERAN GURU DAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS PENDEKATAN KOMUNIKATIF DI SMA NEGERI 1 SESEAN KABUPATEN TORAJA UTARA - Patiung, Dahlia (Inspiratif Pendidikan, 2017)
Abstract: This study aims to examine deeply the application of interactive communicative approaches to the aspects of speaking skills in teaching and learning. The Indonesian language includes (1) the role of teachers, (2) the role of students, and (3) the interaction of teaching and learning. The method used in this research is descriptive method with qualitative paradigm. In collecting data, researchers directly involved observing the natural phenomena that occur in Indonesian language learning in SMA Negeri 1 Sesean North Toraja District. Data collection technique is done by observation, recording, documentation and interview. Data analysis was done by "Data Flow Model Analysis" technique. The result of the research shows that learning of speaking skill based on interactive communicative approach has been done well. In the teaching-learning process the teacher acts as a motivator, communication facilitator, counselor and mediator in teaching and learning activities. The role of students in learning the skills of speaking based on interactive communicative approach has been done well. The role of students in teaching and learning process as a giver and receiver, negotiator and interactor. The shape of the teaching-learning interaction reflects the communicative approach.